Electrode layer-forming curable organopolysiloxane composition, laminate provided with electrode layer, use thereof, and method for producing same
By developing an electrode layer formative curable organopolysiloxane composition without solvent, the problem that the electrode formative composition in the prior art cannot be applied in the solvent-free process is solved, and the stable bonding between the dielectric layer and the electrode layer under high physical displacement conditions is achieved, and the reliability of the equipment is improved.
Patent Information
- Application Number
- CN202380063660.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-11
AI Technical Summary
The existing electrode-forming compositions cannot be effectively applied in solvent-free processes or electrode printing processes, and under high physical displacement conditions, it is easy to cause the interface peeling between the dielectric layer and the electrode layer, affecting the reliability of the equipment.
An electrode layer-forming curable organopolysiloxane composition is developed, which comprises curing reactive organopolysiloxane and conductive particles, and can be uniformly applied by a heating melting process without the use of a solvent, and curing to form an electrode layer at high temperature.
The formation of a uniform and viscoelastic electrode layer in the solvent-free process is achieved, and the following and shape retention between the dielectric layer and the electrode layer is improved, the peeling and defects of the electrode layer are reduced, and the reliability of the equipment is enhanced.
Smart Images

Figure BDA0005296244120000231 
Figure BDA0005296244120000232 
Figure BDA0005296244120000241
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode layer forming curable organopolysiloxane composition, a laminate having an electrode layer formed using the same, uses thereof, a method for producing the same, and a manufacturing apparatus thereof.
[0002] The formative curable organopolysiloxane composition does not require the use of solvents and can be used for solvent-free composition design and process design. It can also form a dielectric layer with good conductivity and good resistance to dielectrics by curing.
[0003] The followable electrode layer. Background Art
[0004] For organopolysiloxane cured products having a polysiloxane skeleton, transparency, electrical insulation,
[0005] It has excellent heat resistance and cold resistance, and can improve electrical activity by introducing high dielectric functional groups such as fluoroalkyl groups as desired. It can also be easily processed into film or sheet form, so it is used in various electrical / electronic
[0006] The adhesive film of the device or the electroactive film of the transducer device such as the actuator is used for various
[0007] These organopolysiloxane cured products are classified into hydrosilylation reaction according to their curing mechanism.
[0008] The curing type, condensation reaction curing type, peroxide curing type, etc. In particular, by leaving it at room temperature
[0009] Since the organopolysiloxane cured product film using the hydrosilylation reaction-curable curable organopolysiloxane composition is rapidly cured by heating and does not generate by-products, the organopolysiloxane cured product film is commonly used.
[0010] On the other hand, in the use of organopolysiloxane cured film as electronic materials such as touch panels,
[0011] Materials, electronic components for display devices, especially transducer materials such as sensors and actuators,
[0012] It is necessary to provide an electrode layer on the electroactive film as a dielectric layer.
[0013] It is proposed that a conductive filler is added to a silicone elastomer matrix having excellent flexibility.
[0014] The electrode layer filled with the filler is used to form an electrode layer having excellent followability to the dielectric layer.
[0015] However, when an electrode layer to which a conductive filler is added is formed on an organopolysiloxane cured film as an electroactive film, interfacial peeling between the dielectric layer and the electrode layer may occur due to displacement of the dielectric layer (e.g., expansion and contraction of an actuator, etc.), which may cause problems during conduction.
[0016] The applicant of this case proposed in Patent Document 1, etc. that an electrode layer as an organopolysiloxane cured film is formed on the electroactive film (= dielectric layer) by coating a curable organopolysiloxane composition containing a conductive filler on the organopolysiloxane cured film as an electroactive film, and a laminated body in which a functional group that participates in a common curing reaction that forms a chemical bond at the interface is used in the dielectric layer / electrode layer forming organopolysiloxane composition in order to improve the followability of the electrode surface as a transducer material such as an actuator (Patent Document 2).
[0017] Prior art literature
[0018] Non-patent literature
[0019] Non-patent literature 1: Kujawski, M.; Pearse, JD; Smela, E. Carbon 2010, 48, 2409-2417.
[0020] Non-patent document 2: Rosset, S.; Shea, HR Appl. Phys. A 2013, 110, 281-307.
[0021] Patent Literature
[0022] Patent Document 1: International Patent Publication No. WO2014 / 105959
[0023] Patent Document 2: International Patent Publication No. WO2022 / 004462 Summary of the invention
[0024] Problems to be solved by the invention
[0025] However, the inventors have found potential problems in these processes. That is, the known electrode-forming compositions are all applied to coating processes in liquid or solvent-using state, and cannot be applied to solvent-free processes or electrode printing processes for the purpose of reducing environmental load and improving the performance of actuators, etc. in recent years. Since the applicable processes are limited, there are potential problems in their industrial development. Further, there is concern that the organic solvent is exposed / remains in the electrode layer obtained by curing and the dielectric breakdown and other characteristics are reduced or the performance is reduced.
[0026] On the other hand, since conventional electrode-forming compositions are applied to coating processes using solvents, the uniformity of the formed electrodes and the ability to follow a practically acceptable substrate are ensured to some extent. However, when the electrode-forming composition is in a solvent-free or non-fluid form, even if an electrode layer is arranged on a dielectric layer, the coating will be uneven, or sufficient viscoelasticity may not be achieved in the obtained electrode layer. In particular, when applied to a transducer with a large physical displacement, there is a strong concern that the shape of the electrode may not be maintained, and its performance may not be fully exerted.
[0027] The present invention is completed to solve the above-mentioned problems, and its purpose is to provide an electrode layer forming composition, a laminate using the same, its use and a manufacturing method. The electrode layer forming composition can be used in a substantially solvent-free process and can be applied to a variety of processes including an electrode printing process (printing). It has excellent handling properties and storage stability. It can be evenly coated by utilizing a heating melting (hot melt) process, etc., and the resulting electrode layer can be solvent-free. It has significantly excellent heat resistance, durability, adhesion to a dielectric layer, tracking properties and shape retention. Even when used in a transducer such as an actuator that is based on a high degree of physical displacement, it is difficult to produce problems such as peeling and defects of the electrode layer, and an electrode layer with viscoelastic properties sufficient for practical use can be formed.
[0028] Solutions for solving problems
[0029] The present inventors conducted intensive research and found that the above-mentioned problems can be solved by using the following electrode layer forming curable organopolysiloxane composition, thereby completing the present invention. The electrode layer forming curable organopolysiloxane composition comprises a curable reactive organopolysiloxane and (E) conductive particles, and the content of the organic solvent is less than 0.1% by mass relative to the entire composition.
[0030] From the perspective of solving the problem, the electrode layer forming curable organopolysiloxane composition of the present invention is preferably a substantially solvent-free type, and does not contain a detectable amount of solvent. Further, from the perspective of being able to achieve viscoelasticity and excellent conductivity of the obtained electrode layer, (E) conductive particles are preferably particles containing at least one conductive carbon selected from carbon nanotubes (CNTs), conductive carbon black, graphite, and vapor-grown carbon (VGCF), and particularly preferably fibrous conductive carbon such as a certain amount of single-walled carbon nanotubes (SWCNTs) is used.
[0031] In addition, the above-mentioned problems are solved by the following laminate and its use (including transducer components, transducers, electronic parts or display devices), wherein the laminate has a structure in which an electrode layer (L2) formed by curing the above-mentioned electrode layer forming curable organopolysiloxane composition is laminated on at least one side of the organopolysiloxane cured film (L1) as a dielectric layer.
[0032] Furthermore, the above-mentioned problems are solved by the following method for manufacturing a laminate and a method for forming an electrode layer in a transducer member including the manufacturing method, the manufacturing method comprising: step I: a step of curing a curable organopolysiloxane composition that imparts a dielectric layer by curing into a film form, thereby obtaining an organopolysiloxane cured product film as a dielectric layer; and step II: a step of applying the above-mentioned electrode layer-forming curable organopolysiloxane composition on the organopolysiloxane cured product film involved in step I or on its precursor to form an electrode layer simultaneously with step I or after step I.
[0033] Effects of the Invention
[0034] According to the present invention, it is possible to provide an electrode layer forming composition, a laminate using the same, and its use and manufacturing method. The electrode layer forming composition can be used in a substantially solvent-free process and can be applied to a variety of processes including printing. Since the composition itself is non-fluid to solid, it is excellent in handling and storage stability, and the heat resistance, durability, adhesion to the dielectric layer, tracking and shape retention of the obtained electrode are significantly excellent. Even when used in a transducer such as an actuator that is based on a high degree of physical displacement, it is difficult to cause the problem of peeling and defects of the electrode layer, and an electrode layer with viscoelastic properties sufficient for practical use can be formed. In particular, according to the present invention, it is possible to provide a flexible process design including a solvent-free process, and it is not easy to cause interface peeling with an organopolysiloxane cured film as a dielectric layer, poor current conduction, and excellent reliability in the use of actuators, etc. The laminate and its manufacturing method can be provided. DETAILED DESCRIPTION
[0035] [Electrode layer forming curable organopolysiloxane composition]
[0036] The electrode layer-forming curable organopolysiloxane composition of the present invention (hereinafter sometimes referred to as "the present composition") comprises a curable reactive organopolysiloxane and (E) conductive fine particles, and contains an organic solvent in an amount of less than 0.1% by mass based on the entire composition.
[0037] [Curing Reactive Organopolysiloxane]
[0038] From the viewpoint of forming a cured product (including a semi-cured product with residual secondary curing reactivity) as an electrode layer by a curing reaction, the present composition includes a curing reactive organopolysiloxane. The curing reaction mechanism of the curing reactive organopolysiloxane is not particularly limited as long as a curing reactant is provided by a crosslinking reaction between siloxane molecules. It can be selected from one or more of a hydrosilylation reaction curing type (including a heating curing reaction and a hydrosilylation reaction using a photoactive hydrosilylation reaction catalyst), a condensation reaction curing type, a peroxide curing type, a high-energy ray curing type such as ultraviolet rays, and a free radical polymerization reaction curing type, and it is possible to use the required curing reactive functional group, a curing agent (including a crosslinking agent and a curing reaction catalyst) according to each curing reaction mechanism. As described later, from the viewpoint that a curing reaction can be carried out at a relatively low temperature and in a short time, and that the control of the reaction is easy, it is preferred that at least a portion of the curing reactive organopolysiloxane is hydrosilylation reactive.
[0039] [Organic solvent content: low-solvent type or solvent-free composition]
[0040] As for the electrode layer forming curable organopolysiloxane composition involved in the present invention, for the composition involved in the present invention, using known detection means such as headspace gas chromatography (GC), the sum of the contents of organic solvents relative to the entire composition is less than 0.1 mass % (= 1000ppm), preferably less than 0.05 mass % (= 500ppm), more preferably less than 0.01 mass % (= 100ppm), and particularly preferably the sum of the contents of organic solvents is less than 0.001 mass % (= 10ppm). In particular, the present composition is preferably evaluated by headspace gas chromatography (GC) as having a sum of the contents of organic solvents less than 10ppm, less than 5ppm, and for each component, it is particularly preferred that the content thereof is less than 5ppm or is below the detection limit (less than 0.1ppm). It should be noted that in the present invention, when the sum of the contents of organic solvents relative to the entire composition is less than 0.1 mass % (= 1000 ppm), it is sometimes called a "low solvent type", and when it is less than 0.001 mass % (= 10 ppm), it can be evaluated as being essentially solvent-free, so it is called a "solvent-free type".
[0041] Specifically, the organic solvent in the present invention is a compound that can dissolve all or part of the components in the present composition. The type of the organic solvent is not particularly limited, and preferably an organic solvent having a boiling point of 80° C. or higher and less than 200° C. is used. More specifically, the organic solvent includes isopropyl alcohol, tert-butyl alcohol, cyclohexanol, cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, toluene, xylene, mesitylene, 1,4-dioxane, dibutyl ether, anisole, 4-methylanisole, benzene, ethylbenzene, ethoxybenzene, ethylene glycol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 2-methoxyethanol (ethylene glycol monomethyl ether), diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, 1-methoxy-2-propyl acetate, 1-ethoxy-2-propyl acetate, octamethylcyclotetrasiloxane, and hexamethyldisiloxane. Halogen-based solvents such as siloxane and the like, trifluorotoluene, 1,2-bis(trifluoromethyl)benzene, 1,3-bis(trifluoromethyl)benzene, 1,4-bis(trifluoromethyl)benzene, trifluoromethylchlorobenzene, trifluoromethylfluorobenzene, hydrofluoroethers and the like, among which, it is particularly preferred that the sum of the contents of one or more organic solvents is less than 0.1% by mass (= 1000 ppm) in practical terms, and in particular, the sum of the contents of one or more organic solvents selected from benzene, toluene, ethylbenzene and xylene is less than 0.1% by mass (= 1000 ppm).
[0042] The composition involved in the present invention is preferably prepared in a manner such that the above-mentioned organic solvent is not added in its manufacturing process. Regarding the organic solvent inevitably mixed into its raw material components, it is practically prepared by reducing the content of the organic solvent by pre-stripping each raw material, or by kneading the present composition at a high temperature to reduce the content of the volatile organic solvent, so that the final sum of the organic solvent contents is less than the above-mentioned lower limit.
[0043] The present composition is substantially free of organic solvents, and has the advantage that no fluorinated solvents, organic solvents, etc. remain in the electrode layer obtained by curing, and the influence of the residual organic solvents on electronic devices can be eliminated. Therefore, the present composition can be used without particular restrictions in solvent-free processes or electrode printing processes for the purpose of reducing environmental load and improving the performance of actuators, etc.
[0044] The present composition is substantially solvent-free, so from the perspective of uniform coating during electrode layer formation, the viscosity and blending amount of each constituent component can be adjusted to design a composition that is liquid or fluid at room temperature (25°C). For example, the electrode layer forming curable organopolysiloxane composition of the present invention can be prepared by selecting a curable reactive organopolysiloxane with relatively low viscosity or fluidity, and adjusting the blending amount of other components including (E) conductive particles to a range in which the composition as a whole can maintain liquid or fluidity at room temperature (25°C) (for example, the overall viscosity of the composition measured using a rotational viscometer is less than 1000 Pa·s, preferably less than 100 Pa·s, and more preferably less than 50 Pa·s).
[0045] On the other hand, the present composition can also be designed to be a non-flowable composition at 25° C. by mixing a certain amount of (E) conductive fine particles, the organopolysiloxane resin described later, a reinforcing filler as solid particles, etc., according to the requirements on the performance of the electrode layer such as the coating process to be applied, conductivity, mechanical strength, and processability, and the requirements related to the temperature dependence of the viscoelasticity of the electrode layer obtained by curing. For example, the present composition can be a low-solvent type or a solvent-free type, and can be arbitrarily designed as a hot-melt type composition.
[0046] In the case where the present composition is a hot-melt composition, the composition is non-fluid (solid or semi-solid) at 25°C and has heating meltability. Specifically, "having heating meltability" means that the softening point of the entire composition is above 50°C, has a melt viscosity at 150°C (preferably a melt viscosity of less than 1000 Pa·s), and has a flowing property. On the other hand, when the softening point is above 200°C, it is above the normal use temperature for molding purposes, etc., and is therefore defined as "not having heating meltability". It should be noted that in this specification, heating meltability is sometimes referred to as "hot meltability".
[0047] When the present composition is a hot-melt composition, it is non-flowable at 25°C. Here, non-flowability means that it does not deform / flow under no load. Preferably, when formed into granules or tablets, it does not deform / flow under 25°C and no load. Such non-flowability can be evaluated, for example, by placing the formed present composition on a hot plate at 25°C, and it does not substantially deform / flow under no load or even if a certain load is applied. This is because if it is non-flowable at 25°C, the shape retention at this temperature is good and the surface adhesiveness is low.
[0048] When the present composition is a hot melt composition, the softening point of the present composition is preferably 100° C. or less. Such a softening point refers to a temperature at which the deformation in the height direction becomes 1 mm or more when a 100-gram load is continuously pressed from above for 10 seconds on a hot plate, and the deformation of the composition is measured after the load is removed.
[0049] When the present composition is a hot-melt composition, from the viewpoint of the viscoelasticity of the electrode layer obtained by using the present composition and the uniform coating property based on the heat melting property, the shear storage modulus (G') of the composition at 100°C before electrode formation (especially before including the curing reaction) is 100℃ ) and shear storage modulus (G') at 25 °C 25℃ ) value ratio (G' 100℃ / G' 25℃ ) is preferably 0.5 or less, more preferably in the range of 0.01 to 0.50, and particularly preferably in the range of 0.02 to 0.45. It should be noted that (G') of the composition after electrode formation (especially after curing reaction) 100℃ / G' 25℃ ) is also preferably less than 0.5, and can be in the range of 0.05 to 0.45, and is preferred. On the other hand, if the composition (G') before or after electrode formation (particularly after curing) is 100℃ / G' 25℃ ) value exceeds 0.5, which means that the temperature dependence of the viscoelasticity of the electrode layer is small, and sometimes there will be performance problems such as being unable to improve processability by heating and maintaining the shape of the electrode layer.
[0050] The viscoelasticity of the electrode layer obtained using the present composition is not particularly limited, but after forming the electrode layer, the shear storage modulus (G') at 25°C is 25℃ ) can be 1.0×10 5 ~7.5×10 6 The range of Pa, in addition to the above-mentioned temperature dependence, can also achieve practically sufficient viscoelasticity of the electrode layer. In addition, from the viewpoint of the viscoelasticity of the electrode layer obtained using the present composition, the value of tanδ of the composition at 25°C before or after electrode formation (especially after curing) is particularly preferably 0.30 or more, and in particular, the value of tanδ of the composition before electrode formation is preferably in the range of 0.35 to 0.99. This is because, when the viscoelasticity of the electrode layer of the present composition or its cured product meets the above conditions, it is not easy to cause the problem of peeling and defects of the electrode layer, and an electrode layer with practically sufficient viscoelastic properties can be formed.
[0051] [Ingredient (E)]
[0052] Component (E) is conductive microparticles, and there is no particular limitation as long as it can impart conductivity to the electrode layer formed using the composition of the present invention. It should be noted that, regarding the electrode layer containing conductive microparticles, for example, the applicant of the present case and others proposed in the International Patent Publication No. WO2014 / 105959, etc., but there is no disclosure about carbon nanotubes (CNTs).
[0053] Specifically, component (E) includes conductive carbon such as carbon nanotubes (CNT), conductive carbon black, graphite (the present invention also includes graphite coated with a conductive material such as metal such as nickel-coated graphite), vapor grown carbon (VGCF), etc.; metal powders such as platinum, gold, silver, copper, nickel, tin, zinc, iron, and aluminum; further examples include antimony-doped tin oxide, phosphorus-doped tin oxide, needle-shaped titanium oxide coated with tin oxide / antimony, tin oxide, indium oxide, antimony oxide, zinc antimonate, and pigments coated with tin oxide on the surface of carbon or graphite whiskers; pigments coated with at least one conductive metal oxide selected from the group consisting of tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), phosphorus-doped tin oxide nickel oxide, and nickel oxide; and conductive pigments containing tin oxide and phosphorus on the surface of titanium dioxide particles, etc., and these may also be treated with various surface treatment agents. These may be used alone or in combination of two or more. In order to uniformly disperse these conductive fine particles in the composition, they may be kneaded in advance with a part or all of the components (A) to (C) used in the composition and formulated in the composition in the form of a composite.
[0054] Furthermore, the conductive inorganic particles can also be particles of conductive materials such as metals coated on the surface of fibers such as glass fibers, silica alumina fibers, alumina fibers, carbon fibers, and needle-shaped reinforcing materials such as aluminum borate whiskers and potassium titanate whiskers, and inorganic fillers such as glass beads, talc, mica, graphite, wollastonite, and dolomite.
[0055] In the composition involved in the present invention, at least a part of component (E) is preferably fine particles containing at least one conductive carbon selected from carbon nanotubes (CNTs), conductive carbon black, graphite and vapor grown carbon (VGCF), and these conductive fine particles have the following advantages: excellent uniform dispersibility in the organopolysiloxane composition, excellent temperature dependence of the viscoelasticity of the electrode layer obtained using the electrode layer forming curable organopolysiloxane composition, and can effectively improve the followability and shape retention of the electrode layer to the dielectric layer.
[0056] In the composition of the present invention, at least a part or all of component (E) is preferably carbon nanotubes (CNTs). CNTs may be single-layer, double-layer, or multi-layer, and their particle size is not particularly limited. It is particularly preferred that (E1) is conductive fine particles comprising single-walled carbon nanotubes (SWCNTs).
[0057] Single-walled carbon nanotubes (SWCNTs) are special types of carbon materials known as one-dimensional materials. Single-walled carbon nanotubes are composed of graphene sheets and are wound in a manner to form a hollow tube with a wall equivalent to the thickness of one atom. By having such a chemical structure and size, among other conductive carbons such as acetylene black, single-walled carbon nanotubes have a tendency to show particularly excellent mechanical properties, electrical properties, thermal properties and optical properties, especially, even if used in small amounts, the volume resistivity of the obtained electrode layer is effectively reduced, and the mechanical strength such as elongation or tensile strength at break of the electrode layer is not damaged, so in addition to the high performance and high strength of the energy density of the electrode layer, it also has the advantage of being able to effectively improve the tracking and shape retention of the electrode layer to the dielectric layer.
[0058] The average outer diameter of the single-walled carbon nanotubes is not particularly limited, but is preferably 2.5 nm or less. It is more preferably 1.0 to 2.5 nm, further preferably 1.1 to 2.0 nm, and particularly preferably 1.2 to 1.8 nm. The average outer diameter of the single-walled carbon nanotubes can be obtained from the light absorption spectrum of the single-walled carbon nanotubes obtained by ultraviolet visible near infrared spectroscopy (UV-Vis-NIR), Raman spectrum, or transmission electron microscope (TEM) image.
[0059] The average fiber length of the single-walled carbon nanotubes is preferably less than 100 μm. It is more preferably 0.1 to 50 μm, further preferably 0.5 to 20 μm, and particularly preferably 1 to 10 μm. The average fiber length of the single-walled carbon nanotubes can be obtained by obtaining an AFM image of the single-walled carbon nanotubes using an atomic force microscope (AFM), or obtaining a TEM image of the single-walled carbon nanotubes using a transmission electron microscope (TEM), measuring the length of each single-walled carbon nanotube, and dividing the total value of the length by the number of single-walled carbon nanotubes measured.
[0060] The G / D ratio of the single-walled carbon nanotube measured by Raman spectroscopy (wavelength 532nm) is preferably 2 or more. It is more preferably 2 to 250, further preferably 5 to 250, particularly preferably 10 to 220, and most preferably 40 to 180. The G / D ratio is the intensity ratio (G / D) of the G band to the D band of the Raman spectrum of the single-walled carbon nanotube. The higher the G / D ratio of the single-walled carbon nanotube, the higher the crystallinity of the single-walled carbon nanotube, and the fewer impurity carbon or defective carbon nanotubes.
[0061] Single-walled carbon nanotubes (SWCNTs) can be obtained as commercial products. In the present invention, for example, TUBALL(TM)MATRIX 601 (polydimethylsiloxane containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 602 (vinyl ether-terminated polydimethylsiloxane containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 201 (fatty acid glycidyl ester containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 202 (aliphatic carboxylic acid ester derivative containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 204 (methacrylate derivative containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 301 (ethoxylated alcohol containing 10% by mass of single-walled carbon nanotubes) (all manufactured by Kusumoto Chemicals Co., Ltd.), etc. can be cited.
[0062] Part or all of the above-mentioned conductive particles may be conductive particles whose surfaces are treated with a part or all of an organosilicon compound. Examples of organosilicon compounds are low molecular weight organosilicon compounds such as silane, silazane, siloxane or the like; and organosilicon polymers or oligomers such as polysiloxane, polycarbosiloxane or the like. Examples of preferred silanes are so-called silane coupling agents. Representative examples of such silane coupling agents are alkyltrialkoxysilanes (methyltrimethoxysilane, vinyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane or the like), trialkoxysilanes containing organic functional groups (glycidyloxypropyltrimethoxysilane, epoxycyclohexylethyltrimethoxysilane, methacryloxypropyltrimethoxysilane, aminopropyltrimethoxysilane or the like). Preferred siloxanes and polysiloxanes include hexamethyldisiloxane, 1,3-dihexyltetramethyldisiloxane, trialkoxysilyl single-terminated polydimethylsiloxane, trialkoxysilyl single-terminated dimethylvinyl single-terminated polydimethylsiloxane, trialkoxysilyl single-terminated organic functional group single-terminated polydimethylsiloxane, trialkoxysilyl doubly terminated polydimethylsiloxane, organic functional group doubly terminated polydimethylsiloxane or the like. When using siloxane, the number n of siloxane bonds is preferably in the range of 2 to 150. In addition, siloxane is not necessarily the main chain, and may also be a siloxane formed by siloxane-modified organic polymers. As an example, silicone-modified acrylic polymers may be cited. Preferred examples of silazanes are hexamethyldisilazane, 1,3-dihexyltetramethyldisilazane or the like. Preferred polycarbosiloxanes are exemplified by polymers having Si-CC-Si bonds in the polymer backbone.
[0063] The amount of component (E) can be appropriately designed according to the conductivity (i.e., volume resistivity), mechanical strength, and shape retention of the obtained electrode layer. However, in practice, the volume fraction of the conductive fine particles (E) relative to the entire composition is preferably in the range of 0.005 to 0.50, and more preferably in the range of 0.005 to 0.25. Within the range of the amount of component (E), the volume resistivity of the electrode layer obtained using the present composition is 10 2 Ω·cm or less, preferably 10 to 10 2 In the range of Ω·cm, there is an advantage that an electrode layer showing excellent conductivity can be designed. In particular, when a part of component (E) is fine particles containing conductive carbon, and in particular, when a part of component (E) is single-walled carbon nanotubes (SWCNT), there is an advantage that the volume resistivity of the electrode layer is effectively reduced to achieve excellent conductivity, and the mechanical strength such as elongation at break or tensile strength of the electrode layer is not impaired, and excellent temperature dependence of its viscoelasticity can be achieved. In particular, the volume fraction of the single-walled carbon nanotubes (SWCNT) relative to the entire composition is preferably in the range of 0.005 to 0.25.
[0064] The present composition is preferably a low-solvent or solvent-free electrode layer forming curable organopolysiloxane composition, particularly a solvent-free composition, at least a portion of the curing reactive organopolysiloxane is hydrosilylation reactive, and at least a portion of the conductive particles as component (E) are particles containing at least one conductive carbon selected from carbon nanotubes (CNTs), conductive carbon black, graphite, and vapor-grown carbon (VGCF). Further, the present composition may be a non-hot-melt type or any of the above-mentioned hot-melt type compositions, and in particular, in the case where the temperature dependence of the viscoelasticity of the electrode layer obtained by curing thereof is required, a hot-melt type composition is preferred.
[0065] The present composition may particularly preferably contain: (A1) a straight-chain organopolysiloxane having curing reactive functional groups containing carbon-carbon double bonds at at least both ends of the molecular chain; (C) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in the molecule: the amount of silicon-bonded hydrogen atoms in this component is 0.1 to 1.5 moles relative to 1 mole of carbon-carbon double bonds in the composition; and (D) an effective amount of a catalyst for a hydrosilylation reaction.
[0066] The details of these components are described later.
[0067] Furthermore, the present composition may optionally include:
[0068] (B) an organopolysiloxane resin having a weight average molecular weight of 5,000 or more in terms of standard polystyrene measured by GPC (gel permeation chromatography) and having M units and Q units in the molecule, and
[0069] (BX) an organopolysiloxane resin having a weight average molecular weight of less than 5000 in terms of standard polystyrene measured by GPC and having M units and Q units in the molecule
[0070] One or more of. It should be noted that, in particular, if the content of component (B) in the composition is 45% by mass or more relative to the entire composition, it is a hot melt type, which has the advantage of improving the temperature dependence of the viscoelasticity of the electrode layer obtained by curing. If the content of component (B) is designed to be 0 to less than 45% by mass relative to the entire composition, the temperature dependence of the viscoelasticity of the electrode layer decreases, and sometimes the viscoelasticity becomes difficult to change, especially at high temperatures above 100°C. Therefore, the presence or absence of component (B) or component (BX) and the amount used can be appropriately designed according to the physical properties of the composition, the required characteristics required for the electrode layer, and the process.
[0071] [Ingredients (A1)]
[0072] Component (A1) is a straight-chain organopolysiloxane having a curing-reactive functional group containing a carbon-carbon double bond at at least both ends of the molecular chain, and the curing-reactive functional group containing a carbon-carbon double bond is selected from an alkenyl group having 2 to 20 carbon atoms such as a vinyl group; a curing-reactive group in a group containing a (meth)acryloyl group such as a 3-acryloxypropyl group and a 3-methacryloxypropyl group, and is particularly preferably an alkenyl group having 2 to 6 carbon atoms.
[0073] The chain organopolysiloxane in component (A1) may contain a group selected from a monovalent hydrocarbon group having no carbon-carbon double bond in the molecule, a hydroxyl group, and an alkoxy group having 1 to 3 carbon atoms. In addition, in the case of the monovalent hydrocarbon group, part of the hydrogen atoms may be substituted by a halogen atom or a hydroxyl group. Industrially, methyl, phenyl, hydroxyl, and alkoxy groups are preferred.
[0074] A preferred component (A1) has at both ends of its molecular chain
[0075] (Alk)R 2 2SiO 1 / 2
[0076] (wherein Alk is an alkenyl group having 2 or more carbon atoms), and the other siloxane units are substantially composed of only R 2 2SiO 2 / 2 A linear organopolysiloxane composed of the siloxane units shown in the formula: 2It is a group selected from the monovalent hydrocarbon group without a carbon-carbon double bond, a hydroxyl group and an alkoxy group, and industrially preferably a methyl group, a phenyl group, a hydroxyl group and an alkoxy group, and all of them may be methyl groups. In addition, the siloxane polymerization degree of component (A1) is in the range of 7 to 1002 including the terminal siloxane unit, and may also be in the range of 102 to 902.
[0077] [Ingredient (B)]
[0078] Component (B) is an optional structure in the present invention, which imparts hot meltability to the composition as a whole, and by using it together with the above-mentioned component (A) within a certain amount range, the composition is imparted with sufficient hot meltability in practical use, and the heat resistance, durability, adhesion to the dielectric layer, followability and shape retention of the obtained electrode are excellent. Specifically, component (B) is an organopolysiloxane resin, which uses an organic solvent such as toluene and xylene, and has a weight average molecular weight of 5000 or more measured by GPC (gel permeation chromatography) in terms of standard polystyrene, and has an M unit and a Q unit in the molecule.
[0079] The amount of component (B) used is arbitrary. The present composition may not contain component (B), or a low molecular weight component (BX) described later may be used. However, when the present composition is a hot-melt composition, the content of component (B) in the composition is preferably 45% by mass or more relative to the entire composition.
[0080] The first characteristic of component (B) is that it is a high molecular weight organopolysiloxane resin having a weight average molecular weight of 5000 or more. From the viewpoint of heat-melting property and shape retention of the obtained electrode, the weight average molecular weight of component (B) is preferably 5500 or more, 6000 or more, and industrially particularly preferably in the range of 5500 to 100,000, 6000 to 50,000. On the other hand, if the weight average molecular weight of component (B) is less than the above lower limit (i.e., low molecular weight organopolysiloxane resin; component (BX) described later), even if a certain amount or more of component (B) containing M / Q units is formulated, as the composition as a whole, it is sometimes impossible to achieve sufficient temperature dependence of viscoelasticity, heat-melting property and shape retention of the electrode.
[0081] The component (B) has R3SiO in the molecule. 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane unit (Q unit) shown may also optionally contain a siloxane selected from R2SiO 2 / 2 (D unit) and RSiO 3 / 2 The siloxane unit in (T unit) is represented by the following average unit formula:
[0082] (R3SiO1 / 2 )p(R2SiO 2 / 2 )q(RSiO 3 / 2 )r(SiO 4 / 2 )s(XO 1 / 2 )t
[0083] The organopolysiloxane resin shown.
[0084] R is a monovalent organic group, and may be a curing reactive group containing a carbon-carbon double bond, or may be a group selected from a monovalent hydrocarbon group, a hydroxyl group, and an alkoxy group that does not have a carbon-carbon double bond in the molecule.
[0085] Specifically, as the curing reactive group containing a carbon-carbon double bond of R, there can be listed alkenyl groups having 2 to 20 carbon atoms selected from vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, undecenyl, dodecenyl and the like; groups containing an acryl group such as 3-acryloxypropyl and 4-acryloxybutyl; and curing reactive groups in groups containing a methacryl group such as 3-methacryloxypropyl and 4-methacryloxybutyl.
[0086] Similarly, as the monovalent hydrocarbon group without a carbon-carbon double bond as R, there can be listed: alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, anthracenyl, phenanthryl, and pyrenyl; aralkyl groups such as benzyl, phenethyl, naphthylethyl, naphthylpropyl, anthracenylethyl, phenanthrylethyl, and pyrenylethyl; and groups in which the hydrogen atoms of these aryl or aralkyl groups are substituted by alkyl groups such as methyl and ethyl; alkoxy groups such as methoxy and ethoxy; and halogen atoms such as chlorine atoms and bromine atoms.
[0087] In the above average unit formula, X is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and OX is a hydroxyl group or an alkoxy group having 1 to 3 carbon atoms. Such a hydrolyzable functional group may be a hydroxyl group remaining in the resin during the synthesis of the organopolysiloxane resin, or may be a structure in which the hydroxyl group in the resin is sealed by treatment with a silazane compound or the like during synthesis.
[0088] Here, p is a positive number, q and r are 0 or positive numbers, s is a positive number, t / (p+q+r+s) is a number in the range of 0 to 0.4, (p+q) / (r+s) is preferably in the range of 0.5 to 2.0, and it is particularly preferred that q and r are 0 and the organopolysiloxane resin consists only of M units and Q units.
[0089] The component (B) in the present invention may be selected from:
[0090] (B1) an organopolysiloxane resin having a curing reactive group containing a carbon-carbon double bond in the molecule, and
[0091] (B2) an organopolysiloxane resin having no curing reactive group containing a carbon-carbon double bond in the molecule
[0092] In one embodiment, the present invention comprises at least one of the organic polysiloxane resins, but from the viewpoint of improving the curing reactivity and the temperature dependence of the viscoelasticity of the obtained electrode layer or the shape retention of the dielectric layer, it is preferred to simultaneously contain these components (B1) and (B2). Specifically, the components (B1) and (B2) can be used in a mass ratio of 5:95 to 95:5, preferably in a mass ratio of 5:95 to 50:50.
[0093] The organopolysiloxane resin as component (B1) preferably includes an organopolysiloxane resin having the above-mentioned weight average molecular weight, the above-mentioned M unit and Q unit, and at least a part of R is an alkenyl group such as vinyl or hexenyl, and the content of the vinyl (CH2=CH-) group is in the range of 1.0 to 5.0% by mass, preferably in the range of 1.2 to 3.5% by mass. It should be noted that R other than the alkenyl group is not particularly limited, but in industry, other R may be an alkyl group such as methyl and an aryl group such as phenyl. It should be noted that the M unit, the Q unit and the optionally included (XO 1 / 2 The preferred ratio and content of the ) units are as described above.
[0094] The organopolysiloxane resin as component (B2) is preferably an organopolysiloxane resin having the above-mentioned weight average molecular weight, having the above-mentioned M unit and Q unit, wherein R is a group selected from alkyl groups such as methyl and aryl groups such as phenyl, and having no curing reactive group containing a carbon-carbon double bond in the molecule. It should be noted that the M unit, the Q unit, and the optionally contained (XO 1 / 2 The preferred ratio and content of the ) units are as described above.
[0095] [Ingredients (BX)]
[0096] The composition of the present invention may optionally contain (BX) a molecular weight of less than 5000 in terms of standard polystyrene and containing R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The organopolysiloxane resin has a siloxane unit (Q unit) shown in FIG. The weight average molecular weight is less than 5000, preferably in the range of 500 to 4500, or in the range of 1000 to 4000. It should be noted that the organopolysiloxane resin may be the same as the component (B) from the viewpoint of other than the molecular weight.
[0097] From the viewpoint of adjusting the viscoelasticity, durability, adhesion to the dielectric layer, followability and shape retention of the electrode layer obtained by the curing reaction of the present composition, the sum of the contents of component (A), component (B) and component (BX) in the entire composition can be in the range of 50 to 95% by mass, preferably 55 to 90% by mass, and more preferably 60 to 90% by mass.
[0098] [Ingredient (C)]
[0099] Component (C) is a crosslinking agent that can form a cured product with the curing reactive group containing a carbon-carbon double bond in component (A) or component (B) / (BX) by a hydrosilylation reaction in the presence of component (D).
[0100] Examples of such component (C) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, methylhydrogenpolysiloxane having trimethylsiloxy groups capped at both ends of the molecular chain, dimethylsiloxane / methylhydrogensiloxane copolymer having trimethylsiloxy groups capped at both ends of the molecular chain, and dimethylsiloxane / methylhydrogensiloxane copolymer having trimethylsiloxy groups capped at both ends of the molecular chain. Dimethylpolysiloxane terminated with dimethylhydrogensiloxy groups, dimethylsiloxane / methylhydrogensiloxane copolymer terminated with dimethylhydrogensiloxy groups at both ends of the molecular chain, methylhydrogensiloxane / diphenylsiloxane copolymer terminated with trimethylsiloxy groups at both ends of the molecular chain, methylhydrogensiloxane / diphenylsiloxane / dimethylsiloxane copolymer terminated with trimethylsiloxy groups at both ends of the molecular chain, hydrolysis condensation product of trimethoxysilane, (CH3)2HSiO 1 / 2 Unit and SiO 4 / 2 The copolymer consists of (CH3)2HSiO 1 / 2 Unit, SiO 4 / 2 Unit and (C6H5)SiO 3 / 2 The invention also includes copolymers composed of these units and mixtures of two or more thereof.
[0101] The amount of component (C) used may be such that the silicon-bonded hydrogen atoms are in the range of 0.1 to 5.0 mol, 0.1 to 1.5 mol, or 0.1 to 1.20 mol per 1 mol of carbon-carbon double bonds in the composition. In particular, if the amount of component (C) used is below the upper limit, the following advantages are achieved: the mechanical strength and temperature dependence of the cured product can be easily designed within a practically appropriate range, and an electrode having a better followability of the electrode layer to the dielectric layer and better shape retention can be easily obtained.
[0102] [Ingredient (D)]
[0103] Component (D) is a catalyst for promoting the hydrosilylation reaction of the curing reactive group containing a carbon-carbon double bond in the present composition with component (C), and examples thereof include: platinum-based catalysts, rhodium-based catalysts, palladium-based catalysts, nickel-based catalysts, iridium-based catalysts, ruthenium-based catalysts, and iron-based catalysts, preferably platinum-based catalysts. Examples of the platinum-based catalyst include: platinum fine powder, platinum black, platinum-supported silica fine powder, platinum-supported activated carbon, chloroplatinic acid, an alcohol solution of chloroplatinic acid, an olefin complex of platinum, an alkenyl siloxane complex of platinum, and platinum-based alkenyl siloxane complexes, and platinum-based alkenyl siloxane complexes are particularly preferred. Examples of the alkenylsiloxane include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, alkenylsiloxanes in which a part of the methyl groups of these alkenylsiloxanes are substituted with ethyl groups, phenyl groups, etc., and alkenylsiloxanes in which the vinyl groups of these alkenylsiloxanes are substituted with allyl groups, hexenyl groups, etc. In particular, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred from the viewpoint of good stability of the platinum-alkenylsiloxane complex. Furthermore, from the viewpoint of being able to improve the stability of the platinum-alkenylsiloxane complex, it is preferred to add alkenylsiloxanes such as 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3-diallyl-1,1,3,3-tetramethyldisiloxane, 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane, 1,3-divinyl-1,1,3,3-tetraphenyldisiloxane, and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and organosiloxane oligomers such as dimethylsiloxane oligomers to the complex, and it is particularly preferred to add alkenylsiloxanes. In addition, from the viewpoint of improving the workability and the pot life of the composition, these hydrosilylation reaction catalysts may also be thermoplastic resin particles containing hydrosilylation reaction catalysts as catalysts dispersed or encapsulated in thermoplastic resins such as silicone resins, polycarbonate resins, and acrylic resins, and in particular thermoplastic resin particles containing hydrosilylation reaction catalysts containing platinum. It should be noted that as a catalyst for promoting the hydrosilylation reaction, non-platinum metal catalysts such as iron, ruthenium, and iron / cobalt can be used.
[0104] In particular, the composition involved in the present invention is a composition for forming an electrode by curing. From the perspective of improving the stability, workability and pot life of the composition during production, at least a part of the component (D) may be thermoplastic resin microparticles containing (D1) a hydrosilylation reaction catalyst containing platinum, and preferably. Such a component (D1) may be microparticles in which a platinum-based hydrosilylation reaction catalyst is dissolved or dispersed in a thermoplastic resin, or microcapsule microparticles having a structure in which a platinum-based catalyst is contained as a core in the shell of a thermoplastic resin. As a platinum-based catalyst, an alkenylsiloxane complex of platinum similar to that described above can be exemplified. In addition, the thermoplastic resin is not particularly limited as long as it does not substantially penetrate the platinum-based catalyst and does not substantially dissolve in the organopolysiloxane of the main component of the present composition at least during production and storage of the present composition, but the softening point or glass transition point of the thermoplastic resin is preferably 80°C or more, and more preferably 120°C or more. Specifically, silicone resins, polysilane resins, epoxy resins, acrylic resins, and methylcellulose polycarbonate resins can be preferably used. The softening point is the temperature at which the resin begins to flow due to its own weight or its own surface tension, and can be measured by observing the crushed particles under a microscope while heating at a certain speed. In addition, the glass transition point can be measured by DSC (Differential Scanning Calorimeter). In the present invention, it is preferred that either the softening point or the glass transition point is above 120°C. This is because if the softening point or the glass transition point of the thermoplastic resin is lower than 120°C, the platinum component may begin to dissolve in the process of uniformly mixing the present composition described later. In addition, the average particle size of the thermoplastic microparticles containing the platinum catalyst is not limited, but is preferably in the range of 0.1 to 500 μm, and more preferably in the range of 0.3 to 100 μm. This is because it is difficult to prepare thermoplastic resin microparticles containing a platinum catalyst having an average particle size less than the lower limit of the above range, and on the other hand, if the upper limit of the above range is exceeded, the dispersibility in the present composition is reduced.
[0105] The method for preparing such thermoplastic resin microparticles containing a hydrosilylation reaction catalyst containing platinum is not limited, and examples thereof include chemical methods such as the conventionally known interfacial polymerization method or in-situ polymerization method, and physical / mechanical methods such as the coagulation method or the in-liquid drying method. In particular, from the viewpoint of relatively easy acquisition of microcapsule microparticles with a narrow particle size distribution, the in-liquid drying method and the gas phase drying method using a spray dryer are ideal. The microparticles obtained by these methods can also be used directly, but in order to obtain a composition with excellent storage stability, it is ideal to wash it with an appropriate washing solvent to remove the platinum catalyst attached to its surface. Here, the appropriate washing solvent refers to a washing solvent having the property of not dissolving the thermoplastic resin but dissolving the platinum catalyst. As such a washing solvent, for example, alcohols such as methanol and ethanol; low molecular weight organopolysiloxanes such as hexamethyldisiloxane, etc. can be cited. The ratio of the catalyst for hydrosilylation reaction to the thermoplastic resin varies greatly depending on the method for producing the granular material, and therefore cannot be particularly limited, but the content of the platinum-based catalyst relative to the thermoplastic resin is preferably 0.01% by mass or more. This is because, when the content of the platinum-based catalyst is less than 0.01% by mass, if the thermoplastic resin particles containing the platinum-based catalyst that are contained in the present composition are not contained in large quantities, the physical properties of the cured product are impaired by the present composition.
[0106] The amount of the hydrosilylation reaction catalyst as component (D) added is a catalytic amount, preferably 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm in terms of metal atoms by mass relative to the entire composition.
[0107] A part or all of the component (D) does not show activity without irradiation with high energy rays, but can be a catalyst for hydrosilylation reaction that shows activity in the composition by irradiation with high energy rays, so-called high energy ray activated catalyst or photoactivated catalyst. By using such a component (D), the composition as a whole can be cured even at low temperatures by irradiation with high energy rays as a trigger, and has excellent storage stability and easy reaction control, thereby achieving excellent workability.
[0108] Examples of high-energy rays include ultraviolet rays, gamma rays, X-rays, alpha rays, electron beams, and the like. In particular, ultraviolet rays, X-rays, and electron beams irradiated by commercially available electron beam irradiation devices are included. Ultraviolet rays are preferred from the perspective of catalyst activation efficiency, and ultraviolet rays with a wavelength of 280 to 380 nm are preferred from the perspective of industrial utilization. In addition, the irradiation amount varies depending on the type of high-energy ray-activated catalyst. In the case of ultraviolet rays, the cumulative irradiation amount at a wavelength of 365 nm is preferably 100 mJ / cm2 ~100J / cm 2 within the range.
[0109] Specific examples of component (D) include (methylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)trimethylplatinum (IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)dimethylethylplatinum (IV), (cyclopentadienyl)dimethylacetylplatinum (IV), (trimethylsilylcyclopentadienyl)trimethylplatinum (IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum (IV), (dimethylphenylsilylcyclopentadienyl)trimethylcyclopentadienylplatinum (IV), trimethyl(acetylacetylacetonate)platinum (IV), trimethyl(3,5 -heptanedione) platinum (IV), trimethyl (methyl acetoacetate) platinum (IV), bis (2,4-pentanedione) platinum (II), bis (2,4-hexanedione) platinum (II), bis (2,4-heptanedione) platinum (II), bis (3,5-heptanedione) platinum (II), bis (1-phenyl-1,3-butanedione) platinum (II), bis (1,3-diphenyl-1,3-propanedione) platinum (II), bis (hexafluoroacetylacetonate) platinum (II), among which (methylcyclopentadienyl) trimethyl platinum (IV) and bis (2,4-pentanedione) platinum (II) are preferred from the viewpoint of versatility and ease of acquisition.
[0110] The amount of the high energy ray activated catalyst used as component (D) is an effective amount and is not particularly limited, but as long as it is an amount that promotes the curing of the composition of the present invention, it is not particularly limited. Specifically, the metal atoms in the catalyst are 0.01 to 1,000 ppm by mass relative to the sum of the components (A) to (C) (the whole is set to 100% by mass), and preferably the platinum metal atoms in the component (D) are in an amount within the range of 0.1 to 500 ppm.
[0111] In the present composition, as long as the purpose of the present invention is not impaired, other optional components may include (F) reinforcing filler, (G) curing retarder, (H) tackifier and (I) organic wax. As described above, since the present composition is a low-solvent or solvent-free composition, even when these optional components are formulated, it is preferred not to use an organic solvent, or to reduce the content of the organic solvent in the composition by heating, kneading, steam stripping, etc. after formulation.
[0112] [Ingredients (F)]
[0113] Component (F) is a reinforcing filler, which can sometimes improve the mechanical strength of the electrode layer obtained using the present composition. Specifically, it is preferably one or more reinforcing inorganic particles with an average primary particle size of less than 50nm, and examples thereof include fumed silica, wet silica, crushed silica, calcium carbonate, diatomaceous earth, finely crushed quartz, various metal oxide powders other than aluminum oxide / zinc oxide, glass fiber, and carbon fiber, etc., and these are treated with one or more organosilicon compounds described later. The shape is not particularly limited, and reinforcing particles of any shape such as particles, plates, needles, and fibers can be used.
[0114] As a preferred example of component (F), hydrophilic or hydrophobic fumed silica or its metal oxide complex having an average primary particle size of 10 nm or less and partially agglomerated can be listed. Furthermore, from the viewpoint of improving dispersibility, it is preferably a substance obtained by treating fumed silica or its metal oxide complex with the above-mentioned organosilicon compound. These reinforcing inorganic particles can also be used in combination of two or more.
[0115] The BET specific surface area of component (F) can be appropriately selected, but may be 10 m 2 / g or more, and can also be 10 to 1000 m 2 / g range. Furthermore, as component (F), two or more reinforcing fillers with different BET specific surface areas may be used in combination. For example, as component (F), (F1) surface-treated with one or more organic silicon compounds and having an average BET specific surface area of more than 100 m 2 / g reinforcing fine particles or a composite thereof and (F2) surface-treated with one or more organic silicon compounds and having an average BET specific surface area of 10 to 100 m 2 The reinforcing fine particles or the composite thereof having an amount within the range of 1:1 to 5:1 may be used in combination with the component (F1) and the component (F2) at any mass ratio.
[0116] Component (F) is preferably surface treated with the above-mentioned organosilicon compound, and preferred organosilicon compounds include one or more selected from hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane. It should be noted that, within the scope of not hindering the technical effect of the present invention, surface treatment with a surface treatment agent other than the organosilicon compound may also be used in combination.
[0117] In the above-mentioned surface treatment, the ratio of the surface treatment agent to the total amount of the filler is preferably in the range of 0.1 mass % to 50 mass %, more preferably in the range of 0.3 mass % to 40 mass %. It should be noted that the treatment amount is the charge ratio of the filler to the surface treatment agent, and the remaining treatment agent is preferably removed after the treatment. In addition, when the treatment is performed as needed, there is no problem in using additives that promote or assist the reaction.
[0118] [Ingredient (G)]
[0119] Component (G) is a curing retarder, and in particular, when the present composition is cured by a hydrosilylation reaction, it can effectively suppress side reactions and further improve the storage stability of the composition of the present invention and the usable time during heating and melting.
[0120] The curing retarder that can be used is not particularly limited in structure and type, and can be selected from known hydrosilylation reaction inhibitors, such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynyl-1-cyclohexanol and other alkynols; 3-methyl-3-pentene-1-yne, 3,5-dimethyl-3-hexene-1-yne and other enyne compounds; tetramethyltetravinylcyclotetrasiloxane, tetramethyltetrahexenylcyclotetrasiloxane and other low molecular weight siloxanes containing alkenyl groups; methyl-tris(1,1-dimethyl-2-propynyloxy)silane, vinyl-tris(1,1-dimethylpropynyloxy)silane and other alkynyloxysilanes. It should be noted that when the composition is produced by a process accompanied by heating such as melt kneading, as component (G), a compound having a boiling point of 200° C. or more at atmospheric pressure can also be used.
[0121] In the case where the present composition is a hot melt composition, it is particularly preferred that component (G) use a compound having a boiling point of 200°C or more at atmospheric pressure. This is because, from the perspective of uniform composition, if a compound with a low boiling point is used as a curing retarder, part or all of the curing retarder will volatilize during the melt kneading process, thereby failing to obtain the desired curing delay effect for the final curable silicone composition. It should be noted that methyl-tris(1,1-dimethyl-2-propynyloxy)silane has a boiling point of 245°C at atmospheric pressure, which is listed as an example of a preferred component (G).
[0122] The amount of component (G) used is arbitrary, but is preferably within a range of 1 to 10000 ppm by mass relative to the entire composition.
[0123] [Ingredient (H)]
[0124] Component (H) is a tackifier, and examples thereof include an organic silicon compound having at least one alkoxy group bonded to a silicon atom in one molecule. Examples of the alkoxy group include: methoxy, ethoxy, propoxy, butoxy, and methoxyethoxy, and methoxy is particularly preferred. In addition, as groups bonded to silicon atoms other than alkoxy groups in the organic silicon compound, examples thereof include: halogen-substituted or non-substituted monovalent hydrocarbon groups such as alkyl, alkenyl, aryl, aralkyl, and halogenated alkyl groups; glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl; glycidoxyalkyl groups such as 2-(3,4-epoxycyclohexyl)ethyl and 3-(3,4-epoxycyclohexyl)propyl; epoxyalkyl groups such as 3,4-epoxybutyl and 7,8-epoxyoctyl; monovalent organic groups containing an acryl group such as 3-methacryloxypropyl; and hydrogen atoms. The organosilicon compound preferably has a group that can react with an alkenyl group or a silicon-bonded hydrogen atom in the present composition, and specifically, preferably has a silicon-bonded hydrogen atom or an alkenyl group. In addition, from the aspect of being able to impart good adhesion to various substrates, the organosilicon compound preferably has at least one monovalent organic group containing an epoxy group in one molecule. Examples of such organosilicon compounds include: organosilane compounds, organosiloxane oligomers, and alkyl silicates. Examples of the molecular structure of the organosiloxane oligomer or alkyl silicate include linear, partially branched linear, branched, cyclic, and reticular, and linear, branched, and reticular are particularly preferred. Examples of the organosilicon compound include silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds each having at least one silicon-bonded alkenyl group or silicon-bonded hydrogen atom and silicon-bonded alkoxy group in one molecule; a silane compound having at least one silicon-bonded alkoxy group or a mixture of a siloxane compound and a siloxane compound each having at least one silicon-bonded hydroxyl group and silicon-bonded alkenyl group in one molecule; a reaction mixture of an amino-containing organoalkoxysilane and an epoxy-containing organoalkoxysilane; an organic compound having at least two alkoxysilyl groups in one molecule and containing bonds other than silicon-oxygen bonds between these silyl groups; a general formula: R a n Si(OR b ) 4-n
[0125] (Where R a is a monovalent organic group containing an epoxy group, R b is an alkyl group having 1 to 6 carbon atoms or a hydrogen atom. n is a number in the range of 1 to 3)
[0126] The epoxy-containing silane or its partial hydrolysis condensate shown, the reaction mixture of the vinyl-containing siloxane oligomer (including the siloxane oligomer of chain or cyclic structure) and the epoxy-containing trialkoxysilane, methyl polysilicate, ethyl polysilicate and ethyl polysilicate containing epoxy group. The tackifier is preferably a low-viscosity liquid, and its viscosity is not limited, but preferably in the range of 1 to 500 mPa·s at 25°C. In addition, the content of the tackifier is not limited, but preferably in the range of 0.01 to 10 parts by mass relative to a total of 100 parts by mass of the present composition.
[0127] In the present invention, as a particularly preferred tackifier, a reaction mixture of an amino-containing organoalkoxysilane and an epoxy-containing organoalkoxysilane can be exemplified. Such a component is a component that improves the initial adhesion to various substrates in contact during the formation of the electrode layer obtained using the present composition (after heating and melting and during the curing process), especially the low-temperature adhesion to the unwashed adherend. Such a reaction mixture is disclosed in Japanese Patent Publication No. 52-8854 and Japanese Patent Publication No. 10-195085.
[0128] Examples of alkoxysilanes having an amino group-containing organic group constituting such a component include aminomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)aminomethyltributoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and 3-anilinopropyltriethoxysilane.
[0129] Examples of the epoxy group-containing organoalkoxysilane include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane.
[0130] The ratio of the alkoxysilane having an organic group containing an amino group to the alkoxysilane having an organic group containing an epoxy group is preferably in the range of (1:1.5) to (1:5), and particularly preferably in the range of (1:2) to (1:4) in terms of molar ratio. This component can be easily synthesized by mixing the alkoxysilane having an organic group containing an amino group and the alkoxysilane having an organic group containing an epoxy group as described above and reacting them at room temperature or under heating.
[0131] In particular, the composition of the present invention preferably contains: when an alkoxysilane having an organic group containing an amino group is reacted with an alkoxysilane having an organic group containing an epoxy group by the method described in Japanese Patent Laid-Open No. 10-195085, in particular, by alcohol exchange reaction, the alkoxysilane is cyclized to form a silane having the general formula:
[0132] [Chemical formula 1]
[0133]
[0134] {In the formula, R 1 is an alkyl group, an alkenyl group or an alkoxy group, R 2 are the same or different and are selected from the general formula:
[0135] [Chemical formula 2]
[0136]
[0137] -R 7 -OR 8
[0138] (Where R 4 is alkylene or alkyleneoxyalkylene, R 5 is a monovalent hydrocarbon group, R 6 is an alkyl group, R 7 is an alkylene group, R 8 is an alkyl, alkenyl or acyl group, and a is 0, 1 or 2. )
[0139] The group consisting of the groups shown in the figure, R 3 are the same or different hydrogen atoms or alkyl groups.
[0140] Examples of such a silazolyl derivative include a silazolyl derivative having a silicon atom-bonded alkoxy group or a silicon atom-bonded alkenyl group in one molecule and represented by the following structure.
[0141] [Chemical formula 3]
[0142]
[0143] (In the formula, Rc is a group selected from methoxy, ethoxy, vinyl, allyl and hexenyl.)
[0144] In the present invention, a silazoline derivative represented by the following structural formula may also be used as a thickener.
[0145] [Chemical formula 4]
[0146]
[0147] R in the formula 1 are the same or different hydrogen atoms or alkyl groups, in particular, as R 1 , preferably a hydrogen atom or a methyl group. 2 is selected from the group consisting of a hydrogen atom, an alkyl group, and a group of the general formula: -R 4 -Si(OR 5 ) x R 6 (3-x) The same or different groups in the group consisting of the organic groups containing alkoxysilyl groups shown in the figure, wherein R 2 At least one of R is an organic group containing an alkoxysilyl group. 2 The alkyl group of R includes, for example, a methyl group. 2 In the organic group containing an alkoxysilyl group, R 4 is a divalent organic group, and examples thereof include alkylene or alkyleneoxyalkylene, and particularly preferably ethylene, propylene, butylene, methyleneoxypropylene, and methyleneoxypentylene. 5 is an alkyl group having 1 to 10 carbon atoms, preferably a methyl group or an ethyl group. 6 is a substituted or unsubstituted monovalent hydrocarbon group, preferably a methyl group. In the formula, x is 1, 2 or 3, preferably 3.
[0148] As such R 2 Examples of the alkoxysilyl-containing organic group include the following groups.
[0149] -(CH2)2Si(OCH3)2(CH2)2Si(OCH3)2CH3
[0150] -(CH2)3Si(OC2H5)2(CH2)3Si(OC2H5)(CH3)2
[0151] -CH2O(CH2)3Si(OCH3)3
[0152] -CH2O(CH2)3Si(OC2H5)3
[0153] -CH2O(CH2)3Si(OCH3)2CH3
[0154] -CH2O(CH2)3Si(OC2H5)2CH3
[0155] -CH2OCH2Si(OCH3)2CH2OCH2Si(OCH3)(CH3)2
[0156] R in the above formula 3is at least one group selected from the group consisting of a substituted or unsubstituted monovalent hydrocarbon group, an alkoxy group having 1 to 10 carbon atoms, a glycidyloxyalkyl group, an ethylene oxide alkyl group, and an acyloxyalkyl group, and R 3 As a monovalent hydrocarbon group, an alkyl group such as a methyl group can be exemplified. 3 The alkoxy group of R includes methoxy, ethoxy, and propoxy. 3 The glycidyloxyalkyl group of R is exemplified by 3-glycidyloxypropyl. 3 The oxiranyl alkyl group of R includes 4-oxiranylbutyl and 8-oxiranyloctyl. 3 Examples of the acyloxyalkyl group include acetoxypropyl and 3-methacryloyloxypropyl. 3 , preferably an alkyl group, an alkenyl group, or an alkoxy group, more preferably an alkyl group or an alkenyl group, and particularly preferably a group selected from a methyl group, a vinyl group, an allyl group, and a hexenyl group.
[0157] The amount of component (H) used is not particularly limited, but is preferably in the range of 0.1 to 1.0 mass %, more preferably 0.2 to 1.0 mass %, based on the entire composition, from the viewpoint of improving adhesion to a dielectric layer or the like.
[0158] [Ingredients (I)]
[0159] Component (I) is an organic wax, specifically, an organic wax with a melting point in the range of 30 to 160°C. Such component (I) can be exemplified by one or more selected from various hot-melt synthetic resins, waxes, fatty acid metal salts, etc. In the case where the present composition is a hot-melt composition, the wax component exhibits a low kinematic viscosity at a high temperature (150°C) to form a melt with excellent fluidity. In addition, by using the above-mentioned components (A), (B), and (E) in combination, the wax component in the melt composed of the present composition can be rapidly extended to the entire composition at a high temperature, thereby exhibiting the following effects: reducing the viscosity of the substrate surface of the composition after melting and the entire composition, and rapidly reducing the surface friction between the substrate and the molten composition, greatly improving the fluidity of the entire composition. Therefore, relative to the total amount of other components, sometimes only by adding a very small amount, the viscosity and fluidity of the molten composition can be greatly improved.
[0160] As long as component (I) satisfies the above-mentioned conditions of the dropping point and the kinematic viscosity when melted, it can also be a petroleum wax such as paraffin, a natural wax such as carnauba wax, a synthetic wax such as montan ester wax, but from the viewpoint of the technical effect of the present invention, it is preferably a hot-melt component composed of a fatty acid metal salt or a fatty acid ester of an erythritol derivative, and is particularly preferably a metal salt of a higher fatty acid such as stearic acid, palmitic acid, oleic acid, isononanoic acid, or pentaerythritol tetrastearate, dipentaerythritol adipic acid stearate, glycerol tri-18-hydroxystearate, pentaerythritol full stearate. Here, the type of the above-mentioned fatty acid metal salt is not particularly limited, and can preferably be exemplified as follows: alkali metal salts such as lithium, sodium, potassium; alkaline earth metal salts such as magnesium, calcium, barium; or zinc salts.
[0161] For the usage of component (I), when the entire composition is set to 100 parts by mass, its content is in the range of 0.01 to 5.0 parts by mass, and can also be 0.01 to 3.5 parts by mass, 0.01 to 3.0 parts by mass. If the usage of the wax component exceeds the above upper limit, the adhesion and mechanical strength of the electrode layer obtained by the composition of the present invention may become insufficient. In addition, if the usage is less than the above lower limit, it may sometimes be impossible to achieve sufficient improvement in fluidity during heating and melting.
[0162] Furthermore, in the present composition, as long as the purpose of the present invention is not impaired, other optional components may include heat-resistant agents such as iron oxide (red iron oxide), cerium oxide, dimethylsilanol cerium, fatty acid cerium salts, cerium hydroxide, and zirconium compounds; dyes, other pigments other than white, flame retardants, heat removers such as aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, and phosphazenes, ion scavengers / pH adjusters such as hydrotalcite, bismuth oxide, or yttrium oxide; flame retardants such as aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, and phosphazenes; hindered phenol compounds, hindered amines, and the like. Antioxidants such as compounds and thioether compounds; soft magnetic particles such as pure iron, silicon steel, iron-cobalt alloy, iron-nickel alloy, iron-chromium alloy, iron-aluminum alloy, carbonyl iron, stainless steel or composite materials containing one or more of these, inorganic flame retardants (such as hydrated metal compounds such as aluminum hydroxide), halogen flame retardants, phosphorus flame retardants, organic metal salt flame retardants, silicone oil, silicone rubber, polyisoprene, 1,2-polybutadiene, 1,4-polybutadiene and other polybutadiene, styrene-butadiene rubber, acrylonitrile-butadiene rubber, carboxyl sealants butadiene acrylonitrile rubber polychloroprene, poly (propylene oxide), poly (oxytetramethylene) glycol, polyolefin glycol, poly-ε-caprolactone and other thermoplastic elastomers, polysulfide rubber, fluororubber and other stress reducing agents, barium titanate (BaTiO3), strontium titanate (SrTiO3), lead zirconate titanate (Pb (Zr, Ti) O3, also known as: PZT), aluminum oxide (Al2O3, also known as: aluminum oxide), zirconium oxide (ZrO2, also known as: zirconium dioxide), magnesium oxide (MgO, also known as: magnesium oxide), silicon dioxide (SiO2, also known as: Dielectric ceramics such as silicon oxide (also known as silicon oxide), titanium dioxide (TiO2, also known as titanium oxide), aluminum nitride (AlN), silicon nitride (Si3N4), silicon carbide (SiC), barium calcium zirconate titanate (also known as BCTZ), polyvinylidene fluoride, etc.; metal salt stabilizers such as cupric chloride, cuprous iodide, cupric acetate, cerium stearate, etc.; antioxidants or heat-resistant stabilizers such as hindered amine series, hindered phenol series, sulfur-containing compound series, acrylate series, phosphorus series organic compounds, etc.; ultraviolet absorbers or weathering agents, light stabilizers, etc. such as benzophenone series, salicylate series, benzotriazole series, etc.
[0163] [Use of the present composition: Formation of electrode layer]
[0164] The form of this composition is not particularly limited. According to its manufacturing process, it can be liquid, or any form of block, solid-semisolid wax, granular, granular, pellet (ingot), or sheet can be adopted. In addition, it is also possible to use a known method to compress a block, solid-semisolid paste, granular, or granular composition into tablets, thereby using it as a pellet-shaped molded product or an ingot-shaped molded product. Similarly, when the composition is a hot-melt type composition, it can be a sheet-shaped molded product obtained by using a single-axis or multi-axis (double-axis, etc.) extruder, etc. to melt-mix the raw materials, and the discharged melt-mixed product can be laminated on a stripping film with a known release layer such as fluorosilicone, etc., or the melt-mixed product can be directly molded into a pellet / ingot shape according to the shape of the discharge port. In particular, this composition itself is non-flowable-solid, so it has the advantages of excellent handling and storage stability.
[0165] The present composition is low solvent type or solvent-free type, and has curing reactivity as a whole composition, so it flows by liquid or any heating and melting process, and can be evenly applied to the position to form the electrode layer, and the curing reaction is carried out at the same time or after the coating, so that the electrode layer composed of the solidified material can be formed. Therefore, it can also be used without restriction in the solvent-free process or electrode printing process for the purpose of reducing environmental load and improving the performance of actuators, etc. Further, the formability, gap filling and adhesion of the present composition during heating and melting are excellent, and the obtained electrode layer is also excellent in addition to heat resistance, durability, adhesion, viscoelastic properties, so particularly in the case of forming the electrode layer formed by using the present composition on the dielectric elastomer sheet, its tracking and shape retention are significantly excellent, even in the case of a transducer that is used as an actuator with a high degree of physical displacement as a prerequisite, it is difficult to produce the problem of peeling or defects of the electrode layer, and has sufficient viscoelastic properties in practical use.
[0166] In the case where the present composition is a hot-melt composition, it can be applied to the part where the electrode layer is to be formed by heating and melting. Specifically, it can be applied to the part where the electrode layer is to be formed by heat distribution, etc. after being heated to above 80°C and melted. It is also possible to arrange a sheet-like molded object at the part where the electrode layer is to be formed and heat it to above 80°C, thereby applying the liquidized composition to the part. It should be noted that the heating and melting temperature is not particularly limited as long as sufficient fluidity, coating properties and gap filling properties can be achieved, and it can be in the range of 80 to 150°C. In the case of having curing reactivity, it is particularly preferred to select the heating and melting temperature according to the type of component (D). For example, if component (D) is thermoplastic resin microparticles containing a platinum-containing hydrosilylation reaction catalyst using a thermoplastic resin having a softening point or a glass transition point of 120°C, the activity of the hydrosilylation reaction can be suppressed in the range of 80 to 120°C. Therefore, within this temperature range, the composition has the advantage of being able to be applied to the portion where the electrode layer is to be formed by heating and melting without any unexpected curing reaction.
[0167] The present composition is a curing reactive composition, and can be applied to the portion where the electrode layer is to be formed after optional heating and melting (including applying by heating and melting after being arranged at the portion where the electrode layer is to be formed in the case of a shaped article such as a sheet), and a curing reaction is allowed to proceed simultaneously with the coating or after the coating, thereby forming an electrode layer composed of a cured product. When components (C) and (D) are used, the curing reaction is a hydrosilylation reaction, and depending on the type of component (D), a heat curing reaction, a curing reaction by irradiation with high-energy rays, and a combination thereof can be selected.
[0168] The temperature of the heat curing reaction is not particularly limited, but is preferably 50°C or more and 200°C or less, more preferably 60°C or more and 200°C or less, and further preferably 80°C or more and 180°C or less. In addition, the time used for the curing reaction is usually 1 second or more and 3 hours or less. In general, a cured product can be obtained by keeping it in the range of 90°C to 180°C for 10 seconds to 30 minutes. It should be noted that, as described above, in the case of selecting thermoplastic resin particles containing platinum hydrosilylation reaction catalysts using thermoplastic resins having specific softening points or glass transition points as component (D), the curing reaction will not proceed at a temperature below the softening point or glass transition point of the thermoplastic resin (wall material), and the curing reaction will proceed rapidly by heating at a temperature above it, so it has the advantage of being easy to control using the temperature of the curing reaction.
[0169] When at least a part of component (D) is the above-mentioned high-energy ray-activated catalyst, the present composition performs a curing reaction by irradiating high-energy rays as a trigger. As active energy rays that can be used for the curing reaction, ultraviolet rays, electron beams, and radiation, etc. can be listed, but ultraviolet rays are preferred in terms of practicality. In the case of using ultraviolet rays for the curing reaction, it is ideal to add a catalyst for the hydrosilylation reaction that has high activity relative to the ultraviolet rays used, such as bis(2,4-pentanedionate) platinum complex and (methylcyclopentadienyl) trimethylplatinum complex. As the ultraviolet light generating source, high-pressure mercury lamps, medium-pressure mercury lamps, Xe-Hg lamps, and deep ultraviolet lamps (Deep UV Lamp) are preferred, and the irradiation amount at this time is preferably 100 to 8,000 mJ / cm 2 .
[0170] The thickness and shape of the electrode layer can be appropriately designed as desired. When having the above-mentioned volume resistance value (conductivity), the electrode layer is in a thin film shape, and the average thickness thereof is preferably in the range of 1 to 100 μm.
[0171] The electrode layer obtained by the curing reaction has excellent viscoelastic properties, and since it is a cured product, there is a tendency to further improve the mechanical strength of the electrode layer itself and the adhesion and followability to the substrate, and by using the electrode layer as the cured product, it has the advantage of being particularly excellent in followability and shape retention. In addition, since the curing reaction is easy to control, flexible process design including solvent-free process can be performed.
[0172] [Uses of the present composition: laminate and dielectric layer]
[0173] The electrode layer obtained using this composition can be used for desired semiconductor components and electronic parts, etc., can be used for electronic components such as semiconductor chips, electronic circuits, semiconductor (including optical semiconductor) devices, etc. without particular restrictions, and can form a laminated body with this electrode layer. In particular, the electrode layer obtained using this composition is excellent in heat resistance, durability, and adhesion, and the temperature dependence of viscoelastic properties is also excellent, so in the case of forming an electrode layer formed using this composition on a dielectric elastomer sheet, its followability and shape retention are significantly excellent, and even if it is used for a transducer with a high degree of physical displacement as a prerequisite, such as an actuator, it is difficult to produce a laminated body of the peeling or defect problem of the electrode layer. It should be noted that the type of dielectric elastomer sheet is not particularly limited, but from the viewpoint of its mechanical strength, heat resistance, flexibility, and electrochemical properties, it is particularly preferably a dielectric layer as an organopolysiloxane cured product film.
[0174] Specifically, a laminate having an electrode layer obtained using the present composition is preferably a laminate having a structure in which an electrode layer (L2) composed of the above-mentioned hot-melt electrode layer-forming organopolysiloxane composition is laminated on at least one side of a (L1) organopolysiloxane cured film as a dielectric layer.
[0175] The cured organopolysiloxane having a polysiloxane skeleton has excellent transparency, electrical insulation, heat resistance, cold resistance, etc., and can be improved in electrical activity by introducing high dielectric functional groups such as fluoroalkyl groups as desired, and can be easily processed into a film or sheet shape. Therefore, it is suitable for use as an adhesive film used in various electrical / electronic equipment or an electroactive film used in transducer devices such as actuators, and is particularly suitable for use as a dielectric layer.
[0176] The curing mechanism of the organopolysiloxane cured film is classified into hydrosilylation reaction curing type, condensation reaction curing type, peroxide curing type, etc. However, since it cures rapidly by being left at room temperature or heated and does not generate by-products, an organopolysiloxane cured film using a hydrosilylation reaction curable curable organopolysiloxane composition is particularly preferred.
[0177] The organopolysiloxane cured film as the dielectric layer is in the form of a thin film, and the average thickness of the film is in the range of 1 to 200 μm, preferably in the range of 1 to 150 μm, and more preferably in the range of 1 to 100 μm. Here, the average thickness of the film is the average value of the thickness at the center of the film. Preferably, the organopolysiloxane cured film is uniform and flat, and in the width direction of the film, it is more preferred that the difference between the thickness at the end and the thickness at the center is within 5.0%, and the average value of the thickness at the center of the film is in the range of 5 to 200 μm.
[0178] Similarly, when the number of internal defects of the organopolysiloxane cured film as the dielectric layer is measured by optical means at an optional position within a unit area of 15 mm×15 mm, the number of internal defects is in the range of 0 to 20, preferably in the range of 0 to 15. If the number of internal defects exceeds the upper limit, dielectric breakdown may occur easily when a high voltage is applied to the film, and the dielectric breakdown strength of the entire film may be significantly reduced.
[0179] The dielectric breakdown strength of the organopolysiloxane cured film as the dielectric layer measured at room temperature is in the range of 56V / μm to 200V / μm, more preferably in the range of 58V / μm to 100V / μm. In addition, the organopolysiloxane cured film of the present invention can also be easily designed to have a specific dielectric constant of 3 or more, 4 or more, 5 or more, or 6 or more at 1kHz and 25°C by introducing an optional amount of a high dielectric functional group such as a fluoroalkyl group and using a high dielectric filler.
[0180] When the organopolysiloxane cured film as the dielectric layer is heat-molded into a sheet with a thickness of 2.0 mm, it can be designed to have the following mechanical properties measured in accordance with JIS K6249.
[0181] (1) At room temperature, the Young's modulus (MPa) can be set to 10 MPa or less, and a particularly preferred range is 0.1 to 2.5 MPa.
[0182] (2) At room temperature, the tear strength (N / mm) can be 1 N / mm or more, and a particularly preferred range is 2 N / mm or more.
[0183] (3) At room temperature, the tensile strength (MPa) can be 1 MPa or more, and a particularly preferred range is 2 MPa or more.
[0184] (4) The elongation at break (%) can be 50% or more, and a particularly preferred range is 100 to 1000%.
[0185] When the cured organopolysiloxane film as a dielectric layer is used as an electronic material such as a touch panel, an electronic component for a display device, and particularly a transducer material such as a sensor, the shear storage modulus at 23° C. is preferably within a range of 10 3 ~10 5 The range of Pa is more preferably 1.0×10 3 ~5.0×10 4 The range of Pa.
[0186] The organopolysiloxane cured film as the dielectric layer has an average thickness of 1 to 200 μm per film as described above, and can be used to form a dielectric layer by laminating a plurality of films to form a laminated film having a thickness exceeding 200 μm.
[0187] [Formation of Laminated Body]
[0188] The above-mentioned laminated body can be preferably obtained, for example, by a method for producing a laminated body comprising the following steps: step I: a step of curing a curable organopolysiloxane composition that imparts a dielectric layer by curing into a film-like shape, thereby obtaining an organopolysiloxane cured product film as a dielectric layer; step II: a step of applying the above-mentioned electrode layer-forming curable organopolysiloxane composition to the organopolysiloxane cured product film or its precursor involved in step I after optionally heating and melting it, and then forming an electrode layer by a curing reaction. It should be noted that, in the application in step II, if the composition is liquid at room temperature, it is directly applied by any means, and if the composition is a hot melt type, in addition to the step of applying the heated and melted composition to the dielectric layer or its precursor and the portion where the electrode layer is to be formed by heat distribution, it also includes a step of placing a sheet-like molded object on the dielectric layer or its precursor and the portion where the electrode layer is to be formed, heating it to 80° C. or above, and applying the liquefied composition to the portion. Furthermore, the formation of the electrode layer includes: forming the electrode layer by cooling the heated and melted composition to dry and solidify it, and forming the electrode layer as a solidified product by causing the heated and melted composition to undergo a curing reaction.
[0189] In particular, when the curing reaction involved in the formation of the dielectric layer involved in the above-mentioned step I and the formation of the electrode layer involved in the step II are curing reactions accompanied by the formation of a cured product, and these curing reactions both include a hydrosilylation reaction, by selecting a composition having different silicon atom-bonded hydrogen atoms (hereinafter sometimes referred to as "SiH / Vi ratio") in the organohydrogenpolysiloxane component relative to 1 mol of the total amount of carbon-carbon double bonds in the curable organopolysiloxane composition involved in the formation of the dielectric layer or the curable organopolysiloxane composition for forming the electrode layer, a structure in which two layers are chemically bonded by a hydrosilylation reaction can be provided at the interface between the dielectric layer and the electrode layer, and the followability and shape retention of the electrode layer involved in the present invention to the dielectric layer can be further improved, and the peeling or defect generation of the electrode layer can be suppressed.
[0190] As an example, regarding the electrode layer-forming curable organopolysiloxane composition according to the present invention, its SiH / Vi ratio ([SiH / Vi] Elec ) is 0.2 mol or more and 1.5 mol or less, preferably 0.3 mol or more and 1.2 mol or less, and more preferably 0.3 mol or more and 1.0 mol or less. For the curable organopolysiloxane composition for forming the dielectric layer, its SiH / Vi ratio ([SiH / Vi] DEAP ) is particularly preferably [SiH / Vi] Elec / [SiH / Vi] DEAPThe value is in the range of 0.33 to 0.85, 0.50 to 0.75, and 0.58 to 0.67. That is, it is particularly preferred that the composition forming the dielectric layer is a combination with a certain degree of excess SiH. This is because, in the case where these curable organopolysiloxane compositions are cured by hydrosilylation reaction, the excess SiH groups present on the dielectric layer side in the interface are easily hydrosilylated with the curable reactive groups containing carbon-carbon double bonds in the electrode layer forming organopolysiloxane composition at the interface of the two layers, and it is easy to give the two layers a chemically bonded structure. This manufacturing method is particularly useful as a method for forming an electrode layer in a transducer component, and can easily provide a dielectric layer and an electrode layer firmly bonded in industry, and is not prone to peeling or defects caused by insufficient bonding strength and tracking properties. Laminated bodies, electronic components or display devices.
[0191] The laminate of the organopolysiloxane cured film of the present invention is useful as an electronic material, a component for a display device or a component for a transducer (including a sensor, a speaker, an actuator and a generator), and can be used as an electroactive film (including a high dielectric film) with an electrode layer, preferably as a component of an electronic component or a display device. Further, as described above, the electroactive film with high dielectric breakdown strength is suitable for transducer components such as actuators as a single layer or a laminated film, and the electrode layer of the present invention can be formed on the dielectric layer without special restrictions even if it is accompanied by a solvent-free process or an electrode printing process of heating and melting, and has excellent tracking and shape retention of the organopolysiloxane cured film as a dielectric layer, and is difficult to produce peeling or defects of the electrode layer. The problem is characterized by being particularly useful for actuators that are started at high voltage.
[0192] It should be noted that the laminate of the cured organopolysiloxane film of the present invention preferably has an electrode layer on one side of the dielectric layer, and has a structure in which these layers are alternately laminated and the entire or partial electrode layer is arranged on the outside. Furthermore, the laminate of the present invention may also have a pressure-sensitive adhesive layer for the purpose of being arranged in a transducer, and a non-silicone thermoplastic resin layer that may optionally have a release surface, in addition to the electrode layer and the single-layer or multi-layer dielectric layer of the present invention.
[0193] Example
[0194] The present invention will be described below with reference to Examples, but the present invention is not limited to these Examples. The following compounds were used in the Examples shown below.
[0195] Component (a1-1): a dimethylsiloxane polymer terminated with vinyldimethylsiloxane groups at both ends (vinyl content: 0.09 mass %, siloxane polymerization degree: 835)
[0196] Component (a1-2): a dimethylsiloxane polymer terminated with vinyldimethylsiloxane groups at both ends (vinyl content: 1.53% by mass, degree of siloxane polymerization: 45)
[0197] Component (b-1): trimethylsilyl units (M) and vinyldimethylsilyl units ( Vi M) and tetrafunctional siloxy units (Q, SiO 4 / 2 ) units (vinyl content: 1.9 mass %, polystyrene-equivalent weight average molecular weight Mw = 2.4 × 10 4 )
[0198] Component (b-2): trimethylsiloxy units (M) and tetrafunctional siloxy units (Q, SiO 4 / 2 ) units (weight average molecular weight in terms of polystyrene measured by GPC using toluene as solvent = 6.4 × 10 3 )
[0199] Component (c-1): dimethylsiloxane polymer terminated with dimethylhydrogensiloxy groups at both ends (content of silicon-bonded water: 0.123 mass %)
[0200] Component (c-2): a dimethylsiloxy-methylhydrogensiloxy-siloxane copolymer terminated with trimethylsiloxy groups at both ends (content of silicon-bonded water: 0.71% by mass).
[0201] Component (d1): Masterbatch containing thermoplastic resin microparticles containing a platinum catalyst (*) Masterbatch containing microparticles containing a platinum catalyst prepared by the method described in the following Reference Example (platinum metal concentration: 0.16 mass %)
[0202] [Reference Example (Preparation of a masterbatch containing thermoplastic resin microparticles containing a platinum catalyst)]
[0203] Into a flask equipped with a stirrer, 900 g of a bisphenol A-type thermoplastic polycarbonate resin (glass transition temperature (Tg) 145°C; wall material), 500 g of toluene, and 4600 g of dichloromethane were added and uniformly mixed. 44.4 g of a divinyltetramethyldisiloxane solution of a platinum (0-valent) divinyltetramethyldisiloxane complex (platinum metal concentration of 5% by mass) was added and mixed to obtain a uniform solution. The solution was sprayed and dried using a spray dryer with nitrogen as a hot air flow to obtain 450 g of spherical thermoplastic resin particles containing a platinum catalyst (average particle size of 1.1 μm).
[0204] <Conductive filler>
[0205] Component (e): single-walled carbon nanotube (SWCNT, 10% by mass in a dimethylsiloxane polymer capped at both ends with trimethylsiloxy groups, TUBALL(TM) MATRIX601)
[0206] <Hydrosilylation Reaction Inhibitor>
[0207] Component (f): 1-ethynylcyclohexanol
[0208] [Examples 1 to 3]
[0209] The composition of each experimental example is shown in Table 1 (Examples). The numerical values corresponding to each component are mass %, and the sum is 100 mass %. In addition, in the following examples, the silicon atom-bonded hydrogen atom (Si-H) of component (c) is used in an amount ranging from 0.46 to 1.00 moles per 1 mole of vinyl (unsaturated hydrocarbon group, the same below) in the composition. Furthermore, physical properties before or after curing measured by the following method are also shown in Table 1.
[0210] [Volume fraction of each component]
[0211] In the present invention, the true density of each component in the composition is defined as follows to calculate the volume fraction: Component (b) is 1.23 g / cc, single-walled carbon nanotubes (SWCNT) in component (e) is 1.58 g / cc, and other components are 0.98 g / cc.
[0212] [Mw of component (b)]
[0213] When the component (b) is mixed and used, Mw is calculated as follows.
[0214]
[0215] In the above formula (1), Mwk and wfk are the Mw of the component (b) ranked at the kth position and its weight fraction in all components (b), respectively.
[0216] [Sample production]
[0217] After weighing the ingredients other than component (d) into a 300cc wide-mouth glass sample bottle, heat it in an oven at 125°C for about 30 minutes. Then, on a hot plate heated to 180°C, scrape off the attachments on the wall of the sample bottle while mixing with an electric stirrer for more than 30 minutes. After cooling, add component (d) and mix with an electric stirrer for more than 30 minutes on a hot plate heated to 120°C while scraping off the attachments. Then, transfer the mixture to a 100cc HDPE container and heat it in an oven at 110°C for more than 10 minutes. Take it out of the oven and mix it at a speed of 2000RPM for more than 4 minutes using a THINKY mixer (ARE-310).
[0218] [Viscoelasticity measurement]
[0219] The storage modulus was measured using a viscoelasticity measuring device (manufactured by Anton-Paar, model MCR302). Each curable composition was placed in an appropriate amount on the lower plate with a Peltier element temperature control system heated to 120°C, a parallel plate with a diameter of 15mm was used, and the sample was set in a manner of about 1.5mm thickness. Under the conditions of frequency 1Hz and deformation 0.1%, after cooling to -20°C at 3°C per minute, the temperature was raised to 150°C and kept for 180 minutes to solidify it. Further, cooling and heating were repeated again. The storage modulus (G') and loss tangent (tanδ) before and after curing at 25°C and 110°C are shown in Table 1. It should be noted that if the ratio of the value of G' before curing at 110°C to the value of G' before curing at 25°C is less than 0.5, it means that the processability is increased by heating.
[0220] [Production of Cured Material]
[0221] A mold of 50 mm long × 50 mm wide × 2 mm thick is placed on a metal plate, and a PTFE film (thickness 150 microns) is placed on it. An appropriate amount of each composition is placed on the PTFE film, and heated in an oven at 120°C for more than 30 minutes. Take it out of the oven, set the PTFE film on the composition, and further clamp it with a metal plate. Then, press-cure at 150°C for 15 minutes, and further post-cure in an oven at 150°C for 45 minutes to obtain a sheet-like cured product.
[0222] [Measurement of solvent component concentration in solidified material]
[0223] The measurement was performed using a headspace gas chromatograph (GC, Agilent GC-7890B / Agilent 7697A). At this time, a calibration curve of the added amount and the GC area value was prepared in advance for each solvent component. Two measurements were performed using approximately 1 g of the solidified sample, respectively. The average values are shown in Table 1. It can be seen that any of the examples contains only a very small amount of residual solvent components.
[0224] [Table 1]
[0225]
[0226]
[0227] [Summarize]
[0228] As described above, in Examples 1 and 2, the temperature dependence of the viscoelasticity of the composition increases before and after curing, and the ratio of the values of G'110°C to G'25°C before curing is 0.5 or less. Therefore, the compositions involved in these Examples do not substantially contain an organic solvent, are easily softened by heating, and have excellent coating properties after hot melting before curing, so even if they are solvent-free, the electrode layer can be uniformly coated on the dielectric layer to form the electrode layer.
[0229] In Example 3 which does not contain component (B), there is essentially no organic solvent, and uniform coating can be performed. Appropriate viscoelasticity can be imparted by heat curing. In particular, even at high temperatures (110°C), the rate of change of viscoelasticity with respect to temperature change is small, and an electrode layer with low temperature dependence of viscoelasticity can be formed.
[0230] In each example, after heating and melting, the wall material of component (d) is heated and cured at a temperature above the glass transition point (Tg) to obtain an electrode layer (film) as a cured product having appropriate viscoelasticity. Here, the volume resistivity of each electrode layer sheet in Examples 1 to 3 is kept low at 10 2 Ω·cm or less, as an electrode layer for various transducers represented by actuators, in addition to having the above-mentioned viscoelastic properties, it also has excellent electrical conductivity. Furthermore, these compositions and the electrode layers obtained by curing have very little residual solvent components, so it can be expected that in the process of manufacturing various transducers represented by actuators, it can prevent the characteristics such as dielectric breakdown caused by solvent exposure and solvent residue, or the performance degradation.
Claims
1. An electrode layer-forming curable organopolysiloxane composition comprising a curable reactive organopolysiloxane and (E) conductive fine particles, The total content of the organic solvent is less than 0.1% by mass based on the entire composition.
2. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The total content of the organic solvent is less than 10 ppm based on the entire composition.
3. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein At least a portion of the curable reactive organopolysiloxane is a hydrosilylation reaction curable organopolysiloxane, and contains: (A1) a linear organopolysiloxane having a curing reactive functional group containing a carbon-carbon double bond at at least both ends of the molecular chain; (C) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in the molecule: the silicon-bonded hydrogen atoms in this component are present in an amount of 0.1 to 1.5 mol per 1 mol of the total amount of carbon-carbon double bonds in the composition; and (D) An effective amount of a catalyst for the hydrosilylation reaction.
4. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The conductive fine particles are fine particles containing at least one conductive carbon selected from the group consisting of carbon nanotubes (CNTs), conductive carbon black, graphite, and vapor grown carbon (VGCF).
5. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The conductive fine particles are fine particles including single-walled carbon nanotubes (SWCNTs).
6. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The volume fraction of the conductive fine particles relative to the entire composition is in the range of 0.005 to 0.50, and the volume resistivity of the electrode layer obtained using the present composition is 10 2 Ω·cm or less.
7. The electrode layer-forming curable organopolysiloxane composition according to claim 3, wherein At least a portion of component (C) is (C1) an organohydrogenpolysiloxane having only silicon-bonded hydrogen atoms at both ends of the molecular chain, and the silicon-bonded hydrogen atoms in component (C) are in an amount of 0.1 to 1.00 mol per 1 mol of the total amount of carbon-carbon double bonds in the composition.
8. The electrode layer-forming curable organopolysiloxane composition according to claim 3, wherein At least a part of the component (D) is (D1) thermoplastic resin fine particles containing a hydrosilylation reaction catalyst containing platinum.
9. A laminate having a structure in which two or more layers of cured organopolysiloxane films having different compositions are laminated, and The present invention has a structure in which (L2) an electrode layer obtained by curing the electrode layer-forming curable organopolysiloxane composition according to any one of claims 1 to 8 is laminated on at least one side of (L1) a cured organopolysiloxane film as a dielectric layer. 10 . A transducer member, comprising the laminated body according to claim 9 . 11 . A transducer comprising the laminate according to claim 9 . 12 . An electronic component or a display device comprising the laminate according to claim 9 .
13. A method for producing a laminate, wherein the laminate is the laminate according to claim 9, the method comprising the following steps: Step I: a step of curing the curable organopolysiloxane composition that provides a dielectric layer by curing into a film form to obtain an organopolysiloxane cured film as a dielectric layer; Step II: A step of applying the electrode layer-forming curable organopolysiloxane composition according to any one of claims 1 to 8 onto the organopolysiloxane cured product film or its precursor in step I simultaneously with or after step I to form an electrode layer. 14 . A method for forming an electrode layer in a transducer member, comprising the method for producing a laminate according to claim 13 .
Citation Information
Patent Citations
JP1977008854B2
Carbasilatrane derivative, its production, adhesion accelerator and hardenable silicone composition
JP1998195085A
Curable organopolysiloxane composition for transducers and applications of such curable silicone composition for transducers
WO2014105959A1
Multilayer body composed of cured organopolysiloxane films, use of same, and method for producing same
WO2022004462A1